2021
DOI: 10.1002/dad2.12200
|View full text |Cite|
|
Sign up to set email alerts
|

Spatio‐spectral relationships between pathological neural dynamics and cognitive impairment along the Alzheimer's disease spectrum

Abstract: Introduction Numerous studies have described aberrant patterns of rhythmic neural activity in patients along the Alzheimer's disease (AD) spectrum, yet the relationships between these pathological features and cognitive decline are uncertain. Methods We acquired magnetoencephalography (MEG) data from 38 amyloid‐PET biomarker‐confirmed patients on the AD spectrum and a comparison group of biomarker‐negative cognitively normal (CN) healthy adults, alongside an extensive neuropsychological battery. Results By mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
(69 reference statements)
2
32
0
Order By: Relevance
“…Finally, care should be taken to interpret the data in the context of the specific analysis that we performed. Notably, the current results represent the difference between EC and EO conditions in normalized spectral units, where each frequency band is quantified as a percentage of the total spectral power, consistent with several previous reports ( Candelaria-Cook et al, 2022 ; Lew et al, 2021 ; Niso et al, 2019 ; Ott et al, 2021 ; Wiesman et al, 2021 , but see Muthuraman et al 2015 who compared absolute power). Given that the total absolute power was greater in the EC compared to EO condition, it is possible that the stronger relative delta, theta, beta, and gamma power in the EO condition could instead show that the distribution of absolute power among the canonical bands differed between the conditions, with alpha having a much larger share of the overall absolute power in the EC relative to the EO condition.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, care should be taken to interpret the data in the context of the specific analysis that we performed. Notably, the current results represent the difference between EC and EO conditions in normalized spectral units, where each frequency band is quantified as a percentage of the total spectral power, consistent with several previous reports ( Candelaria-Cook et al, 2022 ; Lew et al, 2021 ; Niso et al, 2019 ; Ott et al, 2021 ; Wiesman et al, 2021 , but see Muthuraman et al 2015 who compared absolute power). Given that the total absolute power was greater in the EC compared to EO condition, it is possible that the stronger relative delta, theta, beta, and gamma power in the EO condition could instead show that the distribution of absolute power among the canonical bands differed between the conditions, with alpha having a much larger share of the overall absolute power in the EC relative to the EO condition.…”
Section: Discussionsupporting
confidence: 88%
“…Power spectrum densities (PSD) were estimated using Welch’s method ( Welch, 1967 ) on each four-second epoch, with one second sliding Hamming windows overlapping at 50%. The PSDs were then normalized within each frequency band to the total power across the total frequency spectrum per condition, consistent with previous reports on resting state MEG data ( Candelaria-Cook et al, 2022 ; Lew et al, 2021 ; Niso et al, 2019 ; Ott et al, 2021 ; Wiesman et al, 2021 , 2022 ). The PSD maps were then averaged within each participant, separated by the two conditions, and for each of the five frequency bands separately, resulting in 10 PSD maps for each participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…slower activity in the delta and theta bands). 63–65 This is of particular importance, given that these animal studies showing the clearance of amyloid and tau through the use of gamma stimulation and entrainment have yet to be replicated in human patients living with Alzheimer’s disease. Of note, while we found clear relationships between the strength of absolute neural entrainment and MMSE in patients on the Alzheimer’s disease spectrum, we found no significant relationships between specific neuropsychological domains and entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is understood about the impact of disease progression on MEG responses. Many of the MEG studies examining patients on the ADS and those with HAND have focused on resting-state activity [23][24][25][26][27][28], and far fewer MEG studies have used taskbased paradigms to examine disease-specific neural aberrations supporting cognitive processes. The limited previous MEG studies of selective attention in the context of HIV have found altered theta and alpha activity, with theta predicting neuropsychological outcomes and distinguishing cognitively impaired and unimpaired PWH [29].…”
Section: Introductionmentioning
confidence: 99%